Ideological roots of the conflict between pro-Kurdish and pro-Islamic parties in Turkey - Dag, Rahman (Cambridge Scholars Publishing, 2017)
The current agenda of international politics is full of headline-grabbing conflicts. This book focuses on one such conflict, namely the Kurdish question in Turkey, with recent peace negotiations between Turkey and the PKK having apparently failed.